Mechanical Evaluation of Bottom Ash from Municipal Solid Waste Incineration Used in Roadbase - Qiang Tang; Fan Gu; Hui Chen; Cong Lu; Yu Zhang (Advances in Civil Engineering)
As a by-product from the incineration of municipal solid waste, bottom ash has a broad application prospect of resource utilization. In this study, bottom ash was selected as partial aggregate alternative and used as roadbase materials. The cemented aggregate containing bottom ash was evaluated through both experimental and numerical analysis. According to the results, the unconfined compressive strength of samples increases with the curing time, and the failure strain of sample decreases with the curing time. The unconfined compressive strength and failure strain of samples are influenced by the types of bottom ash. The increase of compressive strength with the curing time can be attributed to that the hydration reaction of cement will be more complete when the curing time is longer. The representative value (7 days) of unconfined compressive strength of samples meets the strength requirement (≥2.5 MPa) of the road subbase layer of heavy traffic highway in China. Subsequently, the surface settlement decreases with the increase of the modulus and thickness of roadbase and the distance from the centerline, while the settlement increases with vehicle load increasing. The modulus of the roadbase is not the main influences on the pavement settlement, under the condition that the strength of samples meets the requirements. However, increasing the thickness of roadbase can reduce the settlement at the center of the pavement effectively.